2016
DOI: 10.1080/09540121.2016.1173645
|View full text |Cite
|
Sign up to set email alerts
|

Health-information needs of HIV-positive adults in Latin America and the Caribbean: an integrative review of the literature

Abstract: An assessment of information needs is essential for care planning for patients living with chronic diseases such as human immunodeficiency virus (HIV). The extent to which these assessments have been conducted in Latin America and the Caribbean (LAC) is unknown. The purpose of this study was, therefore, to identify, evaluate, and summarize what research has been conducted to examine patient perceptions of their health-information needs among adults living with HIV in LAC. Using an integrative review methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…A detailed report of the literature review can be found elsewhere (Stonbraker & Larson, ), but in summary, 11 articles from 8 out of 33 countries met inclusion criteria. From these studies, the predominant information needs of PLWH in Latin America and the Caribbean were identified as information about HIV in general (including symptoms, illness trajectory, and laboratory results), more knowledge about HIV medications, and information about other sexually transmitted infections or about secondary (opportunistic) infections.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A detailed report of the literature review can be found elsewhere (Stonbraker & Larson, ), but in summary, 11 articles from 8 out of 33 countries met inclusion criteria. From these studies, the predominant information needs of PLWH in Latin America and the Caribbean were identified as information about HIV in general (including symptoms, illness trajectory, and laboratory results), more knowledge about HIV medications, and information about other sexually transmitted infections or about secondary (opportunistic) infections.…”
Section: Resultsmentioning
confidence: 99%
“…From these studies, the predominant information needs of PLWH in Latin America and the Caribbean were identified as information about HIV in general (including symptoms, illness trajectory, and laboratory results), more knowledge about HIV medications, and information about other sexually transmitted infections or about secondary (opportunistic) infections. How to modify one's lifestyle following a positive diagnosis, methods of effective communication with providers and friends or family members, and effective coping mechanisms were also identified as information needs (Stonbraker & Larson, ). Additional searches conducted for this study did not find any new publications on the information needs of PLWH.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations